Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Unit Security Di PT. KFU Pekanbaru - Yapentra, Arhipen; Desthya, Yanandra Putri (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This  research  was  conducted  at  PT.  Karya  Fia  Utama  Pekanbaru  which  is located on Jl. Garuda No. 57A New East Labuh Pekanbaru, Riau. The purpose of this study was to determine the effect of work discipline on the performance of security unit employees at PT. Work by Fia Utama Pekanbaru. To achieve this goal, a study was conducted using a sample of 35 people, using several methods. First, the simple linear regression test method obtained by the Simple Linear Regression Equation is as follows Y = a + bX. (Y = 31.191 + 0.443X). Second, the Work Discipline t test has a significant effect on the performance of security unit employees at PT. Work by Fia Utama Pekanbaru. This is proven based on the t test found tcount > ttable (3.363 > 2.035). And finally, the magnitude of the influence of the work discipline variable on the performance variable is 25.5%, this is proven based on the results of the Determination Test where an R2 value of0.255 is obtained.